Some aspects of reproductive biology of gangetic ailia, \(Ailia coila\) (Hamilton, 1822) in Bangladesh - David Rintu Das; Mithun, Mahmudul Hasan; Md. Moniruzzaman; Yahia Mahmud (Academia Journal of Biology, 2023)
The present study was conducted by Bangladesh Fisheries Research Institute, Floodplain Sub-station to investigate the reproductive biology of Ailia coila in the northern region of Bangladesh. A total number of 100 fish samples were collected on a monthly basis from the Atrai River and Jamuna River during the period from January 2022 to December 2022. The highest mean value of the gonado-somatic index (GSI) was recorded in July (8.78 ± 1.95%), whereas the lowest was found in December (0.15 ± 0.09%). The highest individual fecundity (2,450 ± 570) and ova diameter (0.38 ± 0.07 mm) was also observed in July. From the histological observation of the ovary, the highest percentages (75%) of mature oocytes were observed during the month of July. Based on the GSI, fecundity and gonadal histology, the breeding season of A. coila was observed from June to August with a remarkable peak in July. In the case of length weight relationship (LWR), the coefficient of determination value (r2) was found 0.96 and the slope was found b = 1.50 which indicated the pattern of negative allometric growth of this species as b < 3. In contrast, an increase was recorded in the fecundity associated with the rise of total length, body weight and gonad weight showed a significant linear relationship. This study would assist in the development of induced breeding techniques and provide valuable information for the sustainable management of this population in the inland open ecosystem.